HeartWare ventricular assist system for bridge to transplant: combined results of the bridge to transplant and continued access protocol trial - Slaughter, Mark S; Pagani, Francis D; McGee, Edwin C; Birks, Emma J; Cotts, William G; Gregoric, Igor; Howard Frazier, O; Icenogle, Timothy; Najjar, Samer S; Boyce, Steven W; Acker, Michael A; John, Ranjit; et al. (The Journal of heart and lung transplantation, 2013)
The HeartWare Ventricular Assist System (HeartWare Inc, Framingmam, MA) is a miniaturized implantable, centrifugal design, continuous-flow blood pump. The pivotal bridge to transplant and continued access protocols trials have enrolled patients with advanced heart failure in a bridge-to-transplant indication. The primary outcome, success, was defined as survival on the originally implanted device, transplant, or explant for ventricular recovery at 180 days. Secondary outcomes included an evaluation of survival, functional and quality of life outcomes, and adverse events. A total of 332 patients in the pivotal bridge to transplant and continued access protocols trial have completed their 180-day primary end-point assessment. Survival in patients receiving the HeartWare pump was 91% at 180 days and 84% at 360 days. Quality of life scores improved significantly, and adverse event rates remain low. The use of the HeartWare pump as a bridge to transplant continues to demonstrate a high 180-day survival rate despite a low rate of transplant. Adverse event rates are similar or better than those observed in historical bridge-to-transplant trials, despite longer exposure times due to longer survival and lower transplant rates.